Toxicity of the bionematicide 1, 4-naphthoquinone on non-target soil organisms. (August 2017) - Chelinho, S.; Maleita, C.M.N.; Francisco, R.; Braga, M.E.M.; da Cunha, M.J.M.; Abrantes, I.; de Sousa, H.C.; Morais, P.V.; Sousa, J.P.
Abstract: The main goal of the present study was to evaluate the ecotoxicological effects of 1, 4-naphthoquinone (1, 4-NTQ), a natural-origin compound presenting nematicidal activity, that can be obtained from walnut husk, in plants and soil invertebrates, including non-target soil nematode communities. This research was part of an ongoing project that aims to develop environmentally-friendly nematicides obtained from agricultural residues. The battery of ISO tests included emergence and growth of corn ( Zea mays ) and rape ( Brassica napus ); avoidance with the earthworm Eisenia andrei and the collembolan Folsomia candida; and reproduction with the previous species plus the enchytraeid Enchytraeus crypticus . A novel soil nematode community assay was also performed. ISO tests and nematode assays were conducted using a natural uncontaminated soil that was spiked with a range of 1, 4-NTQ concentrations. Toxicity of 1, 4-NTQ was found for all test-species and the most sensitive were F. candida and E. andrei . After 7 days of exposure to 1, 4-NTQ, nematode abundance decreased along the concentration gradient, and a partial recovery was observed after 14 days (1, 4-NTQ <48 mg kg −1 soil). The number of nematode families consistently decreased in both periods. Overall, results indicate that a 1, 4-NTQ concentration of <20 mg kg −1 could be environmentally safe but preliminary data suggest that it might be ineffective for the target-nematodes, root-knot nematodes, Meloidogyne spp., and root-lesion nematodes, Pratylenchus spp. In addition, if higher dosages of 1, 4-NTQ bionematicide are necessary, the potential recovery of non-target organisms under real field scenarios also needs to be assessed. Highlights: Effects of 1, 4-naphthoquinone (1, 4-NTQ), a nematicidal compound were assessed. Soil ecotoxicological tests with plants and soil invertebrates were performed. F. candida and E. andrei were the most sensitive speciesto 1, 4-NTQ. A concentration <20 mg 1, 4-NTQ kg −1 of soil seemed to be environmentally safe.